2013
DOI: 10.1038/mp.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Genome-wide association study meta-analysis of European and Asian-ancestry samples identifies three novel loci associated with bipolar disorder

Abstract: Following the online publication of this article, the authors identified an error: only 60% of patients with ADHD (N ¼ 12) were medication-naïve, while the other 40% (N ¼ 8) were free of psychostimulant medication (Methylphenidate: 5 Concerta; 3 Equasym) for 36 h, more than 9 times the half-life of the drug.Genome-wide association study meta-analysis of European and Asian-ancestry samples identifies three novel loci associated with bipolar disorder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A study conducted by Jiang et al in 2019 showed that VPA retrieves the expression of TRANK1 in iPSC-derived neural cells. Prior studies by the same group reported that VPA increased the expression of TRANK1 from shallow baseline levels in immortalized, non-neural cell lines [160]. In this study, they derived neurons and astrocytes from iPSCs generated from fibroblasts of two BD patients, one spinomuscular atrophy I patient, and eight healthy controls.…”
Section: Vpa Treatment In Cellular Models Of Bdmentioning
confidence: 91%
See 1 more Smart Citation
“…A study conducted by Jiang et al in 2019 showed that VPA retrieves the expression of TRANK1 in iPSC-derived neural cells. Prior studies by the same group reported that VPA increased the expression of TRANK1 from shallow baseline levels in immortalized, non-neural cell lines [160]. In this study, they derived neurons and astrocytes from iPSCs generated from fibroblasts of two BD patients, one spinomuscular atrophy I patient, and eight healthy controls.…”
Section: Vpa Treatment In Cellular Models Of Bdmentioning
confidence: 91%
“…Previous GWAS studies have already identified the TRANK1 gene loci to be significantly associated with BD [85,160,161]. A study conducted by Jiang et al in 2019 showed that VPA retrieves the expression of TRANK1 in iPSC-derived neural cells.…”
Section: Vpa Treatment In Cellular Models Of Bdmentioning
confidence: 99%